Tennis one-handed backhand stroke at different impact heights - Zhang, S.; Fuji, N. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to compare the kinematic differences of the racket during a one-handed backhand stroke at different impact heights. Five male collegiate tennis players were instructed to stroke the incoming balls from different heights to a crosscourt target area. The impact heights were classified as High, Middle, and Low. Significant differences were observed at 3 heights for racket angles (p < 0.05). The decrease of the angular velocity of upper trunk right-lateral rotation at High might be the main element that resulted in a decrease in the resultant velocity of the racket at impact. The greater moment of inertia of the dominant arm and racket about shoulder horizontal abduction-adduction axis at High made arm difficult to be accelerated. It might influence the velocity and control of the one-handed backhand stroke at high impact point.